Exploring critical incidents technique on social justice themes with Brazilian physical education teacher-researchers - Flor, Breno José Mascarenhas Sá de; Souza, Rener Victor Oliveira de; Gonçalves, Yasmin; Silva, Jorlany Pereira da; Lopes, Francisco Junielison Correia; Ribeiro, Manoela de Castro Marques; Venâncio, Luciana; Sanches Neto, Luiz (Frontiers in Education, 2024)
This research is qualitatively oriented and aims to analyze themes of social justice -according to the methodology proposed by the international project EduHealth -based on critical incidents in physical education classes. The incidents have been identified by six physical education teacher-researchers who produced vignettes from the situations. Three of them are Master's students from the Postgraduate Program in Physical Education at the Federal University of Rio Grande do Norte (PPGEF-UFRN) and three are from the Professional Postgraduate Program in Physical Education in National Network at the Federal University of Ceará (ProEF-UFC). Both universities are located in the Northeastern region of Brazil. Findings point to themes related to gender inequality, trans invisibility and/or homophobia, socioeconomic inequalities, reflective-critical issues about democracy and social inclusion, the struggle for social rights, bullying, religions and empathy, intellectual and physical disabilities, diversity, identity, and low self-esteem. A critical education based on social justice is essential in facing the analyzed situations. In conclusion, the notion of social justice can help to promote the knowledge that teacher-researchers mobilize to teach physical education's thematic subjects in a contextualized and engaged way. This perspective helps to understand the privileges and unjust power relations present in Brazilian society, pointing out subsidies for reflection and deepening of the teaching and learning processes.